2015
DOI: 10.1111/ijfs.12767
|View full text |Cite
|
Sign up to set email alerts
|

A potential of ultrasound on minerals, micro‐organisms, phenolic compounds and colouring pigments of grapefruit juice

Abstract: Summary The grapefruit juice was sonicated in an ultrasonic bath at 28 kHz frequency (amplitude 70%), for 0, 30, 60 and 90 min at 20 °C. This research was focused on the effects of ultrasound treatment on phenolic compounds, minerals, viscosity, lycopene, total anthocyanins, total carotenoids, micro‐organism analysis and sugars. A statistically significant increase was observed in total carotenoids, lycopene, sugar contents (sucrose, glucose and fructose) and phenolic compounds, whereas a decrease in viscosity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
68
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(71 citation statements)
references
References 41 publications
(51 reference statements)
3
68
0
Order By: Relevance
“…A comparable result was also observed in the work of Bhat, Kamaruddin, Min‐Tze, and Karim () and higher TPC of lime samples following the US application, also an increase in TPC in sonicated pear samples was also pointed out (Cruz‐Cansino et al, ). This change might be correlated with the release of the bound form of phenolic content because of the deformation of the cell wall by the cavitation phenomena (Aadil, Wang, et al, , ).…”
Section: Resultsmentioning
confidence: 99%
“…A comparable result was also observed in the work of Bhat, Kamaruddin, Min‐Tze, and Karim () and higher TPC of lime samples following the US application, also an increase in TPC in sonicated pear samples was also pointed out (Cruz‐Cansino et al, ). This change might be correlated with the release of the bound form of phenolic content because of the deformation of the cell wall by the cavitation phenomena (Aadil, Wang, et al, , ).…”
Section: Resultsmentioning
confidence: 99%
“…The EC values were 3.16, 3.24, and 3.38 ms / cm, respectively, and the SO 2 concentrations (35.90, 35.89, and 35.10 mg / L, respectively) were compared with that of the untreated sample (36.85 mg / L). Overall, the EC of liquid food products is due to the presence of some nutrient components, such as macro‐ and microelements, vitamins, amino acids, and lipids (Aadil et al., ). The acidity of the alcoholic beverages treated by 1.38, 2.02, and 2.92 kV/cm was 0.22, 0.21, and 0.20 g / L, respectively, for VA and 5.05, 4.92, and 4.88 g / L, respectively, for TA.…”
Section: Resultsmentioning
confidence: 99%
“…An analysis of the TAC in apple juice treated by PEF revealed that anthocyanin retention is dependent on polarity, pulsed frequency width, and treatment period during the treatment by PEF (Noci et al., ). The increase in TAC was investigated by the cavitation process that caused disintegrated particles to increase in the diffusion rates (Aadil et al., ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Microwave, high power ultrasound, irradiation, g rays, and pulsed electric field represent some alternative technologies designed to obtain safe foods, while maintaining their nutritional and sensory qualities (Aadil et al, 2015;Engmann, Ma, Tchabo, & Ma, 2014;Ferrario, Alzamora, & Guerrero, 2015). The topic of this paper is the use of ultrasound (US) as an antimicrobial tool.…”
Section: Introductionmentioning
confidence: 99%